Absence of mutagenic activity in the bacterial reverse mutation assay with pulegone and peppermint oil. (8th July 2020) - Bastaki, Maria; Lu, Vivian; Aubanel, Michel; Bialk, Heidi; Choi, Christopher; Demyttenaere, Jan; Diop, Maodo Malick; Etter, Sylvain; Han, Xing; Harman, Christie L; Krammer, Gerhard; Schnabel, Jürgen; et al.
The essential oil of peppermint and one of its natural constituents, (R)-(+)-pulegone, are approved flavorings added to food worldwide. (R)-(+)-Pulegone and peppermint oil were tested separately in two independent bacterial reverse mutation assays according to Organisation for Economic Co-operation and Development Guideline 471. Both flavorings did not produce any evidence of mutagenicity up to cytotoxic concentrations in either the presence or the absence of exogenous metabolic activation.